Pairing Effects in Impure Lattice Dynamics - Stewart, Norman James (My University, 1976)
A study is made of the effects of pairing of defects on the dynamics of impure lattices, with the prospect of calculating the properties of crystals with a reasonably high concentration of impurities. A harmonic theory is used, with a mass-defect model, i.e. mass differences only are considered.
Various parameters of lattice dynamics are studied, such as the atomic mean square displacement, by use of the Green's functions of Zubarev (1960), as evaluated by Bruno (1971).
Finally, a calculation is made of the shifts and widths in the phonon spectrum of Copper due to the addition of 20% Gold impurities. The theory of Aiyer et al. (1969) is used, as corrected by Nickel and Krumhansl (1971), with a derivation along the lines of Langer (1961).
It is shown that pairing effects are small and that the high-concentration calculation does not reproduce the experimental results of Svensson and Kamitakahara (1972) so that a more detailed model must be employed, in particular the inclusion of force constant changes and volume effects appears to be necessary.
Keywords: pairing, impure, lattice, dynamics, crystals, force constant